The effects of bilingualism on children's perception of speech sounds - Brasileiro, I. (LOT, 2009)
The general topic addressed by this dissertation is that of bilingualism, and more specifically, the topic of bilingual acquisition of speech sounds. The central question in this study is the following: does bilingualism affect children’s perceptual development of speech sounds? The term bilingual is used here as synonymous with simultaneously bilingual, i.e. those speakers of (typically) two languages who have been exposed to both languages from birth. This study takes an experimental approach. Bilingual and monolingual children and adults participated on a longitudinal study in which their perception of a Dutch vowel contrast was tested. Participants’ responses were analyzed in terms of cue reliance, i.e. how much they rely on different acoustic cues in their perception of a speech contrast. Anticipating here the major results, this dissertation will show that, although at a certain point in their development bilingual and monolingual children have identical perceptual behavior, they differ in their developmental paths. This finding is in line with the main literature on bilingual perceptual development. However, the findings in this dissertation are unusual in how this difference takes places. Although patterns of bilingual delay and acceleration have both been previously attested, the bilingual learners in the current study show signs of being simultaneously delayed and accelerated in their perception. Specifically, bilingual children show signs of delay in their acquisition of spectral cues and signs of acceleration in their acquisition of durational cues. This dissertation will claim that the difference found between bilingual and monolingual children is the consequence of two factors: (i) the nature of the language input to the learner, which differs for bilingual and monolingual children, and to a smaller degree, (ii) the interaction between the bilinguals’ linguistic systems. The current study adds to our knowledge of speech perception by focusing on a type of learner underrepresented in the literature, that of pre-school aged bilingual children. Although studies on infants abound, little is known about the perceptual development in this age group. Additional strengths of this study lie in the variety of target and control groups involved and their comprehensiveness, including two groups of bilingual children who differ from each other in terms of language dominance, two groups of monolingual children, and two groups of monolingual adults This dissertation is of interest to researchers working on bilingualism, language development and speech perception in general.
Keywords: Preprint